Capacidad de degradación de compuestos fenólicos del complejo enzimático producido por Pleurotus ostreatus (2017)
Water contamination with phenolic compounds, is a problem that has been growing in recent years. This because these compounds seriously affect human health causing intestinal and cardiovascular damage, are considered carcinogenic and may even cause death if ingested. Because these compounds are not easily degradable, complementary methods known as advanced oxidation processes (AOP) have been developed, including fenton, photo-fenton and photo-catalytic processes. These processes are able to remove contaminants at very low concentrations, but at the industrial level, they present limitations because of the high operational costs and the ones associated with the reagents. Recent research has shown that the direct application of enzymes such as laccases can serve the same purpose. The following project evaluates the degradation capacity of phenolic compounds by the enzymatic complex produced by Pleurotus ostreatus. The inoculum was carried out in a semisolid rice husk medium and during 30 days the enzymatic activity and the glucose concentration in the assemblages were monitored in order to relate these parameters to the degradation capacity of phenolic compounds by the enzymatic complex. For the degradation capacity analysis samples were taken on days 15, 20 and 25 of cultivation and mixed with a phenol standard analyzing its degradability at three different temperatures (20, 32 and 42À C). It was obtained that in the 25 day of cultivation and at a temperature of 42À C, the highest percentage of degradation of phenolic compounds was presented, with a value of 29,4% coinciding with the maximum enzymatic activity which was presented on day 25 with a value of 1000 U / L.